PENGARUH NORMALIZING TERHADAP BAJA 20Mn Cr6 HASIL PENGECORAN UNTUK SUPPORT ROLLER - Yusril Irwan Irwan (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Rotary Kiln  machine  is used in fertilizer plant which is function to mix the fertilizer ingredients. Part of the Rotary Kiln is support by using a roller. Support roller is made of 20MnCr6 material, AISI 5120 (0.18% C) with casting process. Normalizing phase on casting processes is using to increase strength of the material The objectives of the normalizes process is to eliminate residual stresses, softening, increasing toughness, homogenization of micro structures and to ease machining processes. The effect of normalizing can be measured by using  mechanical test, ie tensile test, hardness test and microstructure analysis. Test specimens were made the same material with normalizing and without normalizing process. Normalizing process temperature at 900oC heating for 150 minutes with air cooling for 7 hours. The results has shown that normalizing material has lowest tensile strength of 41.05 kgf/mm2 is compared to 42.16 kgf/mm2. However, the ductile fracture is higher 41.2% is compared to 29.52%, the microstructure formed uniformly evenly compared without normalizing. The softening process also makes the roller support rotate due to rubbing with riding ring.